A Challenging Case of Multifocal Mycobacterium marinum Osteoarticular Infection in a Patient with Anorexia Nervosa - Katie Sharff; Zaw Min; Nitin Bhanot (Case Reports in Orthopedics)
Disseminated infection due to Mycobacterium marinum is rare but has been described in immunosuppressed and transplant recipients. We describe a case of multifocal osteoarticular involvement by this pathogen in a patient with anorexia nervosa. Serial surgical debridements and a prolonged course of antimicrobial therapy including intravenous amikacin, imipenem, and oral ethambutol and azithromycin were needed to treat the infection. Cell mediated immune deficits related to the patient’s anorexia nervosa predisposed her to a severe infection with M. marinum. Aggressive surgical intervention in conjunction with multiple antimicrobial agents helped cure the infection.